A difficult to hydrate super-hydrophobic alkaline refractory material and preparation method thereof

By constructing a superhydrophobic organic-inorganic composite protective layer on the surface of alkali refractory materials, the problems of easy cracking, powdering and poor effects of traditional waterproofing methods during use are solved, and efficient waterproofing performance and low energy consumption production process are achieved.

CN116730728BActive Publication Date: 2025-04-29WUHAN UNIV OF SCI & TECH

Patent Information

Application Number
CN202310639006.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-01
Publication Date
2025-04-29
Estimated Expiration
2043-06-01

AI Technical Summary

Technical Problem

Existing alkaline refractory materials are prone to cracking and powdering during manufacturing, storage and construction, and traditional waterproofing methods have problems such as introducing low eutectic phases, large-scale loss of free CaO, and poor hydration resistance.

Method used

The alkaline refractory material is coated with a superhydrophobic organic-inorganic composite protective layer, and the modified solution prepared by mixing organic coupling agent, inorganic micro-nano powder and organic solvent is uniformly coated on the surface of the alkali refractory material, and dried under suitable conditions to form a protective layer with high binding strength.

Benefits of technology

It realizes difficult reaction between alkaline refractory materials and liquid water/water vapor, improves their waterproofing performance, avoids the loss of low eutectic phase and free CaO, and reduces the energy consumption of high-temperature sintering, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116730728B_ABST
    Figure CN116730728B_ABST
Patent Text Reader

Abstract

The present invention provides a difficultly hydrated super-hydrophobic alkaline refractory material and a preparation method thereof, wherein the super-hydrophobic alkaline refractory material is obtained by coating a layer of super-hydrophobic organic-inorganic composite protective layer on the surface of the alkaline refractory material. The difficultly hydrated super-hydrophobic alkaline refractory material provided by the present invention has difficulty in hydrating with liquid water / water vapor, and the protective layer has high bonding strength; the preparation process of the super-hydrophobic alkaline refractory material is simple, does not require high temperature treatment, and is suitable for industrial production. The present invention solves the hydration problem of alkaline refractory materials during storage, transportation, construction, etc., while avoiding the shortcomings of introducing a low eutectic phase, a large amount of free CaO loss, and poor anti-hydration effect in the current alkaline refractory waterproofing method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of refractory materials, and in particular relates to a difficult-to-hydrate super-hydrophobic alkaline refractory material and a preparation method thereof. Background Art

[0002] Basic refractories, primarily composed of MgO and CaO, offer advantages such as high refractoriness, high refractoriness under load, excellent resistance to slag corrosion, and the ability to purify molten steel. They are widely used in the linings of converters, refining furnaces, and cement rotary kilns. However, the hydration of CaO and MgO during manufacturing, storage, and construction can lead to cracking and pulverization of basic refractories. Therefore, the ability to inhibit hydration of basic refractories is crucial for their widespread use.

[0003] There are two main traditional methods for waterproofing alkaline refractory materials: (1) Sintering densification method, which reduces the porosity of refractory materials by secondary calcination or adding sintering aids (such as SiO2, Al2O3, etc.), promotes grain development, and thus improves the hydration resistance of refractory materials. However, on the one hand, the introduction of additives will form a low eutectic phase with CaO / MgO, reducing the high-temperature performance of refractory materials; on the other hand, during densification sintering, a large amount of free CaO is easily passivated and cannot play its role in purifying molten steel; thirdly, high-temperature sintering consumes a lot of energy. (2) Surface treatment method: This method forms a physical protective layer on the surface of magnesium-calcium refractory materials through surface treatment with inorganic substances (carbonates, phosphates, etc.) or organic substances (paraffin, stearic acid, etc.), achieving the effect of isolating water vapor. However, the structure of this physical protective layer is relatively loose, making it difficult to form a dense coating layer, and it is easy to fall off locally, resulting in protection failure. Therefore, there is an urgent need to develop new methods for waterproofing alkaline refractory materials and prepare alkaline refractory materials that are difficult to hydrate. Summary of the Invention

[0004] The present invention aims to overcome the shortcomings of existing methods for waterproofing alkaline refractory materials, such as the introduction of a low eutectic phase, a large loss of free CaO, and poor anti-hydration effect, and provides a difficult-to-hydrate super-hydrophobic alkaline refractory material and a preparation method thereof. The surface of the super-hydrophobic alkaline refractory material is coated with a super-hydrophobic organic-inorganic composite protective layer, which has difficulty in hydrating with liquid water / water vapor during storage, transportation, and construction, and the protective layer has high bonding strength. The preparation method has low cost, simple synthesis process, high production efficiency, low energy consumption, and is suitable for industrial production.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] Provided is a difficult-to-hydrate super-hydrophobic alkaline refractory material, which is obtained by coating the surface of an alkaline refractory material with a super-hydrophobic organic-inorganic composite protective layer.

[0007] According to the above scheme, the basic refractory material is a refractory material powder, aggregate or product containing magnesium oxide and / or calcium oxide, wherein the particle size of the powder is 45 to 2500 mesh; the particle size of the aggregate is one of 0 to 1 mm, 1 to 3 mm and 3 to 5 mm; and the porosity of the product is 8 to 25%.

[0008] According to the above scheme, the contact angle between the surface of the super hydrophobic alkaline refractory material and water is 130-170°, and the hydration weight gain rate is 0-5% when placed under the conditions of 50°C ambient temperature and 90% relative humidity for 10 hours.

[0009] According to the above scheme, the organic-inorganic composite protective layer is obtained by uniformly coating an organic-inorganic composite modified solution obtained by mixing an organic coupling agent, inorganic micro-nano powder and an organic solvent on an alkaline refractory material and then drying it. The coverage rate of the organic-inorganic composite protective layer on the surface of the alkaline refractory material is 65-100%.

[0010] According to the above scheme, the organic coupling agent contains both A group and B group, wherein the A group is one of hydrocarbon group, ester group, siloxane group and phenyl group, and the B group is one of carboxyl group, amino group, phosphate group and silane group.

[0011] Preferably, the organic coupling agent is one of lauric acid, cinnamic acid, myristic acid, n-dodecylphosphoric acid, n-octylamine, phenylenediamine, n-octyltriethoxysilane and dodecyltrichlorosilane. The organic coupling agent is industrial pure or analytical pure.

[0012] According to the above solution, the inorganic micro-nano powder is one or more of aluminum oxide, zirconium dioxide, titanium oxide, lanthanum oxide and yttrium oxide, is industrial pure or analytical pure, and has a particle size of ≤10 μm.

[0013] According to the above scheme, the organic solvent is one of methanol, ethanol, toluene, acetone and acetonitrile, and is industrial pure or analytical pure.

[0014] According to the above scheme, the mass ratio of the organic coupling agent to the inorganic micro-nano powder is 1:0.1-20.

[0015] According to the above solution, the mass ratio of the total mass of the organic coupling agent and the inorganic micro-nano powder to the solvent is 1:10-100.

[0016] The present invention also provides a method for preparing the above-mentioned difficult-to-hydrate super-hydrophobic alkaline refractory material, the specific steps of which are as follows: mixing an organic coupling agent, an inorganic micro-nano powder and an organic solvent to obtain an organic-inorganic composite modified solution, then uniformly coating the obtained organic-inorganic composite modifier solution on the alkaline refractory material, and then drying to obtain the difficult-to-hydrate super-hydrophobic alkaline refractory material.

[0017] According to the above scheme, the organic-inorganic composite protective layer is coated on the alkaline refractory material by dipping, spraying, brushing or roller mixing process.

[0018] According to the above scheme, the impregnation process conditions are: impregnation at 0-60°C for 0.5-5 hours.

[0019] According to the above scheme, the spraying process conditions are: under environmental conditions of 10-40°C and relative humidity of 30-70%, the spray gun pressure is 0.01-0.5MPa, the spraying distance is 0.01-0.5m, the spray gun moving speed is 0.01-0.5m / s, and the spraying time is 0.5-3 minutes.

[0020] According to the above scheme, the brush coating process conditions are: under environmental conditions of 10-40°C and relative humidity of 30-70%, the moving speed is 0.01-0.5m / s, and the number of brush coatings is 1-10 times.

[0021] According to the above scheme, the process conditions of the roller mixing are: under the environmental conditions of 10-40°C and relative humidity of 30-70%, the ball-to-material ratio is 1-20:1, the roller speed is 10-100rpm, and the roller time is 0.5-10 hours.

[0022] According to the above scheme, the drying conditions are: heating at 20-100° C. for 12-48 hours.

[0023] This application uses a superhydrophobic modification on alkaline refractory materials. Using an organic coupling agent containing hydrophobic groups and good film-forming properties as the binding phase and inorganic micro-nano powders as the surface roughening agent, a high-strength superhydrophobic organic-inorganic composite protective layer is constructed on the alkaline refractory materials through dipping, spraying, brushing, or roller mixing processes. The A group in the organic coupling agent imparts hydrophobic properties to the alkaline refractory materials, while the B group coordinates with the Mg / Ca atoms and hydroxylated Mg / Ca–OH groups on the alkaline refractory surface, ensuring the interfacial bonding strength between the organic-inorganic composite protective layer and the alkaline refractory materials.

[0024] The present invention is based on constructing a super-hydrophobic surface to prevent the hydration of alkaline refractory materials. Its super-hydrophobic organic-inorganic composite protective layer does not require 100% physical coating on the alkaline refractory material. The entire process does not require high-temperature treatment, which reduces energy consumption. The hydrophobic groups of the super-hydrophobic protective layer inhibit the intrinsic moisture absorption capacity of the alkaline refractory material; at the same time, the inorganic micro-nano powder fills some of the open pores on the surface while regulating the surface roughness of the alkaline refractory material and increasing its water contact angle, further inhibiting the diffusion of water vapor in the air into the interior of the alkaline refractory material by "blocking the pores". The two work together to achieve the difficult hydration of super-hydrophobic alkaline refractory materials.

[0025] The beneficial effects of the present invention are:

[0026] 1. The super-hydrophobic organic-inorganic composite protective layer provided by the present invention can achieve the difficulty of the alkaline refractory material to react with liquid water / water vapor without 100% physical coating on the alkaline refractory material, showing excellent water-repellent ability; at the same time, it avoids the shortcomings of the current anti-hydration method such as the introduction of low eutectic phase, large loss of free CaO and poor anti-hydration effect.

[0027] 2. Under high temperature, the inorganic micro-nano powders "filling" the pores on the surface of the super-hydrophobic alkaline refractory material can react with the organic coupling agent to degrade the residual components and MgO / CaO in situ to form a ceramic bonding phase. On the one hand, it helps to improve its ability to resist erosion by molten steel and erosion by slag. On the other hand, it passivates the alkaline refractory material and improves its resistance to hydration during high-temperature service.

[0028] 3. The present invention uses organic coupling agents and inorganic micro-nano powders as raw materials for super-hydrophobic modifiers, which are widely available and low in cost. Dipping, spraying, brushing or roller mixing processes are used as modification methods. No high-temperature treatment is required, the process flow is simple, suitable for industrialization, and has high economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a photograph of the water contact angle of the initial unmodified magnesium-calcium aggregate in Example 1 of the present invention;

[0030] Figure 2 This is a SEM photo of the difficult-to-hydrate super-hydrophobic magnesium-calcium aggregate prepared in Example 1;

[0031] Figure 3 This is a photo of the water contact angle of the difficult-to-hydrate superhydrophobic magnesium-calcium aggregate prepared in Example 1. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments, which does not limit the scope of protection thereof.

[0033] Example 1

[0034] A difficult to hydrate super-hydrophobic alkaline refractory material, the preparation method of which is as follows:

[0035] According to the mass ratio of dodecyltrichlorosilane:alumina (particle size D 50 =3μm):ethanol=1:5:200 to prepare an organic-inorganic composite modification solution, 1 mass part of magnesium-calcium aggregate (particle size 0-1mm, CaO content of 30wt.%) was immersed in 5 mass parts of the prepared organic-inorganic composite modification solution, and the mixture was immersed at 25°C for 2 hours. After being taken out, it was dried at 80°C for 48 hours to obtain a difficult-to-hydrate super-hydrophobic alkaline refractory material.

[0036] The initial water contact angle of the unmodified magnesium-calcium aggregate in this embodiment is 0°. Figure 1 As shown; the SEM of the modified super-hydrophobic magnesium-calcium aggregate is as shown Figure 2 As shown in Figure 2, after image processing, it can be estimated that the coverage of the organic-inorganic composite protective layer on its surface is about 92%; the water contact angle of the superhydrophobic magnesium-calcium aggregate is 150°, as shown in Figure 2. Figure 3 This indicates that the magnesium-calcium aggregate is transformed from superhydrophilic to superhydrophobic after being modified by the method of this embodiment.

[0037] The difficult-to-hydrate super-hydrophobic alkaline refractory material prepared in this embodiment was placed at an ambient temperature of 50°C and a relative humidity of 90% for 10 hours, and the initial unmodified magnesium-calcium aggregate was used as a control sample. The hydration weight gain rate was measured to be 0.8%, while the hydration weight gain rate of the initial unmodified magnesium-calcium aggregate was 7.3%.

[0038] After high-temperature heat treatment, the super-hydrophobic alkaline refractory material prepared in this embodiment forms a ceramic bonding phase on the surface of the magnesium-calcium aggregate.

[0039] Example 2

[0040] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the alkaline refractory material used is a magnesium-calcium product (CaO content is 30 wt.%) with a porosity of 14%.

[0041] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate super-hydrophobic magnesium-calcium product prepared in this embodiment is 75%, the water contact angle is 154° (the water contact angle of the initial unmodified magnesium-calcium product is 3°), and the hydration weight gain rate is 0.3% (the hydration weight gain rate of the initial unmodified magnesium-calcium product is 5.3%).

[0042] Example 3

[0043] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the alkaline refractory material used is a magnesium-calcium aggregate with a particle size of 0-1 mm (CaO content of 70 wt.%).

[0044] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium-calcium aggregate prepared in this embodiment is 87%, the water contact angle is 154° (the water contact angle of the initial unmodified magnesium-calcium aggregate is 3°), and the hydration weight gain rate is 3.8% (the hydration weight gain rate of the initial unmodified magnesium-calcium aggregate is 12.3%).

[0045] Example 4

[0046] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the alkaline refractory material used is 325-mesh magnesium-calcium fine powder (CaO content is 30 wt.%).

[0047] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium-calcium fine powder prepared in this embodiment is 95%, the water contact angle is 156° (the water contact angle of the initial unmodified magnesium-calcium fine powder is 3°), and the hydration weight gain rate is 1.2% (the hydration weight gain rate of the initial unmodified magnesium-calcium fine powder is 9.3%).

[0048] Example 5

[0049] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the alkaline refractory material used is made of 325-mesh calcium oxide fine powder.

[0050] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate super-hydrophobic calcium oxide fine powder prepared in this embodiment is 98%, the water contact angle is 150° (the water contact angle of the initial unmodified calcium oxide fine powder is 3°), and the hydration weight gain rate is 5.8% (the hydration weight gain rate of the initial unmodified calcium oxide fine powder is 20.3%).

[0051] Example 6

[0052] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the alkaline refractory material used is made of 325-mesh magnesia fine powder.

[0053] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium oxide fine powder prepared in this embodiment is 98%, the water contact angle is 156° (the water contact angle of the initial unmodified magnesium calcium fine powder is 3°), and the hydration weight gain rate is 0.8% (the hydration weight gain rate of the initial unmodified magnesium calcium fine powder is 7.3%).

[0054] Example 7

[0055] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the organic coupling agent used is n-dodecyl phosphoric acid and the inorganic micro-nano powder is titanium oxide.

[0056] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium-calcium aggregate prepared in this embodiment is 79%, the water contact angle is 150° (the water contact angle of the initial unmodified magnesium-calcium aggregate is 3°), and the hydration weight gain rate is 1.5% (the hydration weight gain rate of the initial unmodified magnesium-calcium aggregate is 5.3%).

[0057] Example 8

[0058] A difficult-to-hydrate super-hydrophobic alkaline refractory material is prepared in the same manner as in Example 1, except that the organic solvent used is acetone.

[0059] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium-calcium aggregate prepared in this embodiment is 70%, the water contact angle is 153° (the water contact angle of the initial unmodified magnesium-calcium aggregate is 3°), and the hydration weight gain rate is 1.4% (the hydration weight gain rate of the initial unmodified magnesium-calcium aggregate is 7.3%).

[0060] Example 9

[0061] A difficult to hydrate super-hydrophobic alkaline refractory material, the preparation method of which is as follows:

[0062] An organic-inorganic composite modification solution was prepared according to the mass ratio of dodecyltrichlorosilane:alumina:anhydrous ethanol of 1:5:200;

[0063] Under environmental conditions of 25°C and 40% humidity, the spray gun pressure was set to 0.05MPa, the spray gun distance was 0.25m, the moving speed was 0.1m / s, and the spraying time was 1 minute; 1 part by mass of the above-prepared organic-inorganic composite modified solution was sprayed on 1 part by mass of a magnesium-calcium product (porosity of 20%; CaO content of 50wt.%), and then dried at 70°C for 24 hours to obtain a difficult-to-hydrate super-hydrophobic magnesium-calcium product.

[0064] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate super-hydrophobic magnesium-calcium product prepared in this embodiment is 85%, the water contact angle is 151° (the water contact angle of the initial unmodified alkaline refractory material is 0°), and the hydration weight gain rate is 1.2% (the hydration weight gain rate of the initial unmodified magnesium-calcium product is 5.3%).

[0065] Example 10

[0066] A difficult to hydrate super-hydrophobic alkaline refractory material, the preparation method of which is as follows:

[0067] An organic-inorganic composite modification solution was prepared according to the mass ratio of dodecyltrichlorosilane: zirconium dioxide: anhydrous ethanol of 1:5:200;

[0068] Under environmental conditions of 30°C and 50% humidity, the brush movement speed was set to 0.2m / s and the number of brushings was 5 times. A brush with a diameter of 100mm and a bristle length of 0.25mm was used to brush 2 parts by mass of the above-prepared organic-inorganic composite modified solution on 1 part by mass of a magnesium-calcium product (porosity of 12%; CaO content of 50wt.%), and then dried at 50°C for 48 hours to obtain a difficult-to-hydrate super-hydrophobic magnesium-calcium product.

[0069] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate super-hydrophobic magnesium-calcium product prepared in this embodiment is 90%, the water contact angle is 151° (the water contact angle of the initial unmodified alkaline refractory material is 2°), and the hydration weight gain rate is 2.2% (the hydration weight gain rate of the initial unmodified magnesium-calcium product is 8.3%).

[0070] Example 11

[0071] A difficult to hydrate super-hydrophobic alkaline refractory material, the preparation method of which is as follows:

[0072] An organic-inorganic composite modification solution was prepared according to the mass ratio of dodecyltrichlorosilane: zirconium dioxide: anhydrous ethanol of 1:5:200;

[0073] Under environmental conditions of 15°C and 30% humidity, the ball-to-material ratio was set to 5:1, the roller speed was 100 rpm, and the roller time was 3 hours. A roller mixing process was used to fully mix 1 part by mass of magnesium-calcium aggregate (particle size 0-1 mm, CaO content 70 wt.%) with 3 parts by mass of the above-prepared organic-inorganic composite modified solution, and then dried at 85°C for 24 hours to obtain a difficult-to-hydrate superhydrophobic magnesium-calcium aggregate.

[0074] The coverage of the organic-inorganic composite protective layer on the surface of the difficult-to-hydrate superhydrophobic magnesium-calcium aggregate prepared in this embodiment is 90%, the water contact angle is 154° (the water contact angle of the initial unmodified magnesium-calcium aggregate is 3°), and the hydration weight gain rate is 4.8% (the hydration weight gain rate of the initial unmodified magnesium-calcium aggregate is 12.3%).

Claims

1. A difficult to hydrate super-hydrophobic alkaline refractory material, characterized in that: The super-hydrophobic alkaline refractory material is obtained by coating the surface of the alkaline refractory material with a super-hydrophobic organic-inorganic composite protective layer; The basic refractory material is a refractory product containing magnesium oxide and / or calcium oxide, and the porosity of the product is 8-25%; The organic-inorganic composite protective layer is obtained by uniformly coating an organic-inorganic composite modified solution obtained by mixing an organic coupling agent, an inorganic micro-nano powder and an organic solvent on an alkaline refractory material and then drying the solution. The coverage of the organic-inorganic composite protective layer on the surface of the alkaline refractory material is 65-100%. The organic coupling agent contains both an A group and a B group, wherein the A group is one of a hydrocarbon group, an ester group, a siloxane group and a phenyl group, and the B group is one of a carboxyl group, an amine group, a phosphate group and a silane group; the inorganic micro-nano powder is one or more of aluminum oxide, zirconium dioxide, titanium oxide, lanthanum oxide and yttrium oxide, and is industrial pure or analytical pure, with a particle size of ≤10 μm; The mass ratio of the organic coupling agent to the inorganic micro-nano powder is 1:0.1-20; the mass ratio of the total mass of the organic coupling agent and the inorganic micro-nano powder to the solvent is 1:10-100.

2. The difficultly hydrated super-hydrophobic alkaline refractory material according to claim 1, characterized in that: The contact angle between the surface of the super hydrophobic alkaline refractory material and water is 130-170°, and the hydration weight gain rate is 0-5% when placed under the conditions of 50°C ambient temperature and 90% relative humidity for 10 hours.

3. The difficultly hydrated super-hydrophobic alkaline refractory material according to claim 1, characterized in that: The organic solvent is one of methanol, ethanol, toluene, acetone and acetonitrile, and is industrial or analytically pure.

4. A method for preparing a difficultly hydrated super-hydrophobic alkaline refractory material according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: an organic coupling agent, an inorganic micro-nano powder and an organic solvent are mixed to obtain an organic-inorganic composite modified solution, and then the obtained organic-inorganic composite modifier solution is evenly coated on an alkaline refractory material, and then dried to obtain a difficultly hydrated super-hydrophobic alkaline refractory material.

5. The method for preparing the difficultly hydrated super-hydrophobic alkaline refractory material according to claim 4, characterized in that: The organic-inorganic composite protective layer is coated on the alkaline refractory material by dipping, spraying, brushing or roller mixing process.

6. The method for preparing the difficultly hydrated super-hydrophobic alkaline refractory material according to claim 5, characterized in that: The dipping process conditions are as follows: dipping at 0-60°C for 0.5-5 hours; the spraying process conditions are as follows: under environmental conditions of 10-40°C and relative humidity of 30-70%, the spray gun pressure is 0.01-0.5MPa, the spraying distance is 0.01-0.5m, the spray gun moving speed is 0.01-0.5m / s, and the spraying time is 0.5-3 minutes; the brushing process conditions are as follows: under environmental conditions of 10-40°C and relative humidity of 30-70%, the moving speed is 0.01-0.5m / s, and the number of brushing times is 1-10 times; the roller mixing process conditions are as follows: under environmental conditions of 10-40°C and relative humidity of 30-70%, the ball-to-material ratio is 1-20:1, the roller speed is 10-100rpm, and the roller time is 0.5-10 hours.

7. The method for preparing the difficultly hydrated super-hydrophobic alkaline refractory material according to claim 4, characterized in that: The drying conditions are: heating at 20-100° C. for 12-48 hours.

Citation Information

Patent Citations

  • Composite super-hydrophobic agent as well as preparation method and application thereof

    CN115974453A

  • Ceramic powders with surface which is made hydrophobic and their production and use

    CN1172467A

Cited By

  • Periclase-high-entropy spinel composite refractory material and preparation method thereof

    CN122010579A